The institutional context changes of Village- owned enterprises in Indonesia towards the implementation of participative governance and social enterprise business models / Rudy Suryanto ... [et al.] - Suryanto, Rudy; Mohamed, Nafsiah; Yaya, Rizal; Md Som, Ayub (Accounting Research Institute (ARI), 2022)
This research explains how Village-owned Enterprise (VOE) in Indonesia underwent institutional changes as a response to the institutional context changes and local village responses. The objective of this research was to provide evidence if any village has the capacity to interpret and formulate responses to institutional context changes. A detailed case study of VOE Panggung Lestari in Panggungharjo Village, Yogyakarta, Indonesia was documented by interviewing local leader and key actors in the process of VOE establishment and development. In depth interview with the key person in the Ministry of Village was done to understand the context and issues regarding the institutional context changes in VOE. This research provides a conceptual framework to demonstrate how institutional context changes of regulations, social, market failure and culture might trigger the Panggungharjo Village to provide local solutions to the waste problem by implementing the social enterprise business model and participative governance. This finding adds a new understanding of how a village might escape from the embedded institutional environment by interpreting and responding to the institutional changes to find innovative and sustainable solutions for their local problem, which in this case was the waste problem.